EDUCATIONAL IMPACTS AND ETHICS OF AI FOR 2024 UIN INFORMATION SYSTEMS STUDENTS - Azramedia Indonesia (Jurnal Multidisipliner Bharasumba, 2026)
This study aims to examine the impact and ethics of using artificial intelligence (AI) in the learning process of 2024 Information Systems students at UIN Syarif Hidayatullah Jakarta. The research methodology employs a Systematic Literature Review (SLR) and quantitative surveys. Survey results indicate that AI provides a significant positive impact, including improved efficiency in completing academic tasks and supporting effective understanding of learning materials. However, from an ethical standpoint, findings from the literature review of previous studies reveal serious challenges regarding academic integrity. Literature data shows that 61% of students in collectivist countries tend to consider AI as an acceptable learning assistant despite the risks of plagiarism. Furthermore, literature reviews found that 74% of higher education institutions in developing countries lack explicit guidelines on AI use. Therefore, strengthening digital ethics education and establishing institutional regulations are essential to ensure technological utilization that upholds scientific honesty.